2008
DOI: 10.1103/physreve.77.041109
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo study of the droplet formation-dissolution transition on different two-dimensional lattices

Abstract: In 2003 Biskup [Commun. Math. Phys. 242, 137 (2003)] gave a rigorous proof for the behavior of equilibrium droplets in the two-dimensional (2D) spin-1/2 Ising model (or, equivalently, a lattice gas of particles) on a finite square lattice of volume V with a given excess delta M identical with M-M 0 of magnetization compared to the spontaneous magnetization M 0=m0V . By identifying a dimensionless parameter Delta(delta M) and a universal constant Delta c , they showed in the limit of large system sizes that for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 41 publications
3
45
0
Order By: Relevance
“…The possibility of using an order parameter akin to the m sq in Eq. (14) had also been suggested by Lipowski [9], who confirmed that it appeared to possess the correct behaviour in a small simulation.…”
Section: Fuki-nuke Like Order Parameterssupporting
confidence: 59%
See 1 more Smart Citation
“…The possibility of using an order parameter akin to the m sq in Eq. (14) had also been suggested by Lipowski [9], who confirmed that it appeared to possess the correct behaviour in a small simulation.…”
Section: Fuki-nuke Like Order Parameterssupporting
confidence: 59%
“…1 we show the full time series for the magnetisation m and the fuki-nuke parameter m x abs of the multicanonical measurements for an intermediate (L = 20) and the largest (L = 27) lattice size in the simulations along with the system energy. The time series of the energy per system volume e = E/L 3 of the larger lattice can be seen to be reflected numerous times at e −0.9 (coming from the disordered phase) and e −1.2 (coming from the ordered phase) which shows qualitatively that additional, athermal and non-trivial barriers may be apparent in the system [14]. It is clear that the standard magnetisation is not a suitable order parameter, since it continues to fluctuate around zero even though the system transits many times between …”
Section: Simulation Resultsmentioning
confidence: 93%
“…49 In Fig. 10, we represent the total elastic energy of the spin crossover systems as a function of the relative size of the LS domain and for different ratios of the major and minor axes of the ellipse.…”
Section: Modelmentioning
confidence: 99%
“…16) When all quantities are normalized to the total number of spins, the Δ parameter requires a geometric correction factor α = 2/ √ 3 ≈ 1.075, which is just the inverse square root of the hexagonal unit cell volume √ 3/2 for links of unit length. Hence, here we have to plot λ against…”
Section: Nn Triangular Latticementioning
confidence: 99%
“…And (ii ) does the Ising model with an extended range of interaction or on different two-dimensional lattice types behave similarly? To answer these questions we have performed Monte Carlo computer simulations for increasing system sizes of (i ) square lattices with NN interactions 12), 16) and (ii ) next-nearest-neighbour (NNN) interactions as well as of triangular lattices with NN interactions. 16) In addition, we also analyzed in case (i ) the finite-size scaling behaviour of the associated free-energy barrier.…”
Section: §1 Introductionmentioning
confidence: 99%